The Effects of Lifestyle on The Incidence of Obesity Experienced by Many People: A Literature Review - Azzahroh, Fitrotul Ainiyyah; Tanggono, Aninda (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Obesity is a condition where a person's body exceeds normal weight due to the accumulation of excess body fat tissue. Obesity is caused by the amount of energy released by the body being less than the amount of food ingested. Someone who is obese can easily be measured using BMI. A person who has a BMI > 25.0 can be said to be overweight or obese (Nandar et al., 2019) in the journal Annurullah 2021. This literature aims to review the literature regarding the relationship between obesity and individual lifestyle patterns using a comparison of the best methods. The method used in this journal is by taking samples obtained from the BMI value index and using qualitative statistical methods. The resulting review of journal literature shows that obesity has a significant negative effect on exercise, physical activity and diet. Meanwhile, obesity has a significant positive effect on anxiety levels. It can be concluded that obesity is an abnormal condition in fat that can cause more serious health problems. Understanding the relationship between obesity and the factors that cause it really needs to be studied in more depth. In this journal method, it can be concluded that obesity has a positive and significant effect on exercise, physical activity and healthy diet, which means that the higher the physical activity, exercise and healthy diet, the lower the level of obesity.